Comparison of environmental risk factors for esophageal atresia, anorectal malformations, and the combined phenotype in 263 German families - Zwink, Nadine; Holland-Cunz, Stefan (Diseases of the esophagus, 2016)
Esophageal atresia with or without tracheoesophageal fistula (EA/TEF) and anorectal malformations (ARM) represent the severe ends of the fore- and hindgut malformation spectra. Previous research suggests that environmental factors are implicated in their etiology. These risk factors might indicate the influence of specific etiological mechanisms on distinct developmental processes (e.g. fore- vs. hindgut malformation). The present study compared environmental factors in patients with isolated EA/TEF, isolated ARM, and the combined phenotype during the periconceptional period and the first trimester of pregnancy in order to investigate the hypothesis that fore- and hindgut malformations involve differing environmental factors. Patients with isolated EA/TEF (n = 98), isolated ARM (n = 123), and the combined phenotype (n = 42) were included. Families were recruited within the context of two German multicenter studies of the genetic and environmental causes of EA/TEF (great consortium) and ARM (CURE-Net). Exposures of interest were ascertained using an epidemiological questionnaire. Chi-square, Fisher’s exact, and Mann-Whitney U-tests were used to assess differences between the three phenotypes. Newborns with isolated EA/TEF and the combined phenotype had significantly lower birth weights than newborns with isolated ARM (P = 0.001 and P < 0.0001, respectively). Mothers of isolated EA/TEF consumed more alcohol periconceptional (80%) than mothers of isolated ARM or the combined phenotype (each 67%). Parental smoking (P = 0.003) and artificial reproductive techniques (P = 0.03) were associated with isolated ARM. Unexpectedly, maternal periconceptional multivitamin supplementation was most frequent among patients with the most severe form of disorder, i.e. the combined phenotype (19%). Significant differences in birth weight were apparent between the three phenotype groups. This might be attributable to the limited ability of EA/TEF fetuses to swallow amniotic fluid, thus depriving them of its nutritive properties. Furthermore, the present data suggest that fore- and hindgut malformations involve differing environmental factors. Maternal periconceptional multivitamin supplementation was highest among patients with the combined phenotype. This latter finding is contrary to expectation, and warrants further analysis in large prospective epidemiological studies.
Gesehen am 18.10.2017